DISTRIBUTION OF PHYTONEMATODES REPRESENTATIVES OF THE ORDER TYLENCHIDA (FILIPJEV, 1934) THORNE, 1949 IN THE APPLE ORCHARDS OF THE SURKHANDARYA REGION OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides data on the distribution of phytonematodes by representatives of the order Tylenchida (Filipjev, 1934) Thorne, 1949 in the apple orchards of the Surkhandarya region of Uzbekistan. As a result of the study, 28 species of phytonematodes were identified in the root system and root soil of apple plants. During the research, species dominated Filenchus filiformis, Psilenchus hilarulus, Ditylenchus intermedius, D. myceliophagus, D.triformis, Tylenchorhynchus cylindricus, Bitylenchus dubius, Quinisulcius capitatus, Merlnius brevidens, Rotylenchus robustus, Helicotylenchus dihystera, H.erythrinae, Pratylenchus pratensis, Paratylenchus hamatus and Ditylenchus dipsaci.